2016
DOI: 10.1155/2016/1684190
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the Grading System for Voiding Cystourethrograms in the Management of Vesicoureteral Reflux: An Interrater Comparison

Abstract: Aim. Vesicoureteral reflux (VUR) is one of the most common conditions seen in pediatric urology. Fortunately, there are many treatment options for this disorder. The grading system for VUR varies among doctors, and the literature on its reliability is sparse. Here, we assessed the effectiveness of the current VUR grading system. Methods. A series of 40 voiding cystourethrogram (VCUG) studies were selected. Four pediatric urologists (PU) and four pediatric radiologists (PR) independently graded each VCUG and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…US abnormalities were documented by a consultant radiologist. VUR grading was done after MCUG procedure as per the standards [9]. DMSA scan was done by nuclear medicine specialist.…”
Section: Methodsmentioning
confidence: 99%
“…US abnormalities were documented by a consultant radiologist. VUR grading was done after MCUG procedure as per the standards [9]. DMSA scan was done by nuclear medicine specialist.…”
Section: Methodsmentioning
confidence: 99%
“…However, inter-rater variability is common with this assessment. Some studies have reported favorable intraclass correlation coefficient (ICC) values between 0.8 and 0.9, but lower levels of inter-rater agreement (50–60%) have also been reported ( 39 42 ). To improve the reliability of results, a standardized protocol should be adhered to when performing this assessment ( 37 , 43 ).…”
Section: Diagnosis and Assessmentmentioning
confidence: 99%
“…At a pediatric‐centered hospital, VCUG results would be interpreted by pediatric radiologists who report detailed information about the anatomy and function of both upper and lower urinary tracts using checklists to describe technical (catheter size, contrast medium, the manner of instillation and whether it was a cyclic study), anatomical (VUR presence, grade, bladder shape and urethral image) and functional information (bladder filling and emptying) . However, there are still discrepancies in the interpretation of VUR grade 2–4 among radiologists and urologists, especially for VUR grade 3 and 4 . These differences would influence VUR treatment decisions.…”
Section: Correct Interpretation Of Vcugmentioning
confidence: 99%